2019
DOI: 10.1002/cpe.5651
|View full text |Cite
|
Sign up to set email alerts
|

A platform architecture for occupancy detection using stream processing and machine learning approaches

Abstract: SummaryContext‐awareness in energy‐efficient buildings has been considered as a crucial fact for developing context‐driven control approaches in which sensing and actuation tasks are performed according to the contextual changes. This could be done by including the presence of occupants, number, actions, and behaviors in up‐to‐date context, taking into account the complex interlinked elements, situations, processes, and their dynamics. However, many studies have shown that occupancy information is a major lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…There are particular places that were considered in at least one study (1.07%), such as hospital rooms [ 57 ], a bus [ 58 ], an elderly caring institution [ 59 ], and a university gym [ 12 ]. Furthermore, in six studies (6.45%), specially designed places were used to carry out experiments [ 24 , 55 , 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are particular places that were considered in at least one study (1.07%), such as hospital rooms [ 57 ], a bus [ 58 ], an elderly caring institution [ 59 ], and a university gym [ 12 ]. Furthermore, in six studies (6.45%), specially designed places were used to carry out experiments [ 24 , 55 , 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…People NO YES 1 min GcForest Accuracy 86% [ 11 ] 4 D Detection, Levels NO YES 5 min FNN Accuracy 83.6–94.3% [ 65 ] 10 D Detection, Num. People YES NO 30 min BN Accuracy 82–91% [ 91 ] 15 D Num.People NO YES 1 min RF, ELM RMSE of RF 2.75–10.44 Accuracy of ELM 67.92–69.17% [ 63 ] 1 D Detection NO YES Dynamic ML [ 68 ] 12 D Num. People NO YES 5 min ANN, MLR 96.5–97.5% …”
Section: Table A1mentioning
confidence: 99%
“…The second category [45][46][47][48] uses temperature, humidity, and an infrared camera. The third category uses temperature, humidity and a carbon dioxide sensor data [32,[49][50][51][52][53][54][55][56][57][58]. It is observed that over the years, smart HVAC systems' performance has gradually improved through advanced control strategies whereby ambient conditions and occupants' energy profiles become an integral part of the system.…”
Section: Classification Based On Sbems Technologymentioning
confidence: 99%
“…The development of many data processing and IoT technologies has created a new development opportunity for data fusion. Furthermore, several problems related to energy management can be solved using data fusion methods, such as occupancy prediction, load forecast, predictive control, and occupants’ comfort scenarios [ 16 , 17 , 18 ]. In fact, most machine learning algorithms that have recently emerged for data fusion and prediction intend improve the performance of different services, such as healthcare, urban road planning, and energy management systems [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%